Revolutionizing Global Accounting Epistemology in the Era of Industry 5.0 - Mehra, Rohan (CV. Lafadz Jaya, 2025)
The advent of Industry 5.0 marks a paradigm shift in industrial systems, focusing on human-centric innovation, sustainability, and ethical responsibility. Unlike Industry 4.0, which emphasized automation and efficiency, Industry 5.0 integrates human creativity and values with advanced technologies. This transformation requires a reevaluation of accounting’s epistemological foundations. Traditional accounting, rooted in positivism and quantitative measurement, must adapt to a more pluralistic and ethical framework. In response to the evolving demands for non-financial disclosures, such as environmental, social, and governance (ESG) factors, accounting must integrate both financial and non-financial knowledge to support strategic decision-making. Additionally, with the rise of artificial intelligence (AI) and big data, the role of accountants is evolving from mere data processors to ethical interpreters and decision-makers. This article explores how Industry 5.0 impacts accounting theory and practice, highlighting the need for new epistemological models that incorporate social responsibility, technological ethics, and stakeholder engagement. The research suggests that accounting must become a tool not only for financial transparency but also for sustainable and ethical governance, ensuring it meets the complex demands of the modern industrial landscape.